Individual Differences in Tendencies Toward Internet Use Disorder, Internet Literacy and Their Link to Autistic Traits in Both China and Germany - Zhang, YingYing; Sindermann, Cornelia; Kendrick, Keith M.; Becker, Benjamin; Montag, Christian (Frontiers in Psychiatry, 2021)
Recent evidence demonstrates that Internet Use Disorder tendencies (IUD; formerly known as Internet Addiction) are associated with higher tendencies towards autistic traits. In the present study, we therefore aimed to further explore this association between Internet Use Disorder tendencies and autistic traits in a large cohort of German and Chinese subjects (total N=1,524; mostly student background) who completed the short Internet-Addiction-Test, Autism-Spectrum-Quotient (AQ), and the Internet-Literacy-Questionnaire. Moreover, the present research also enabled us to study potential differences in the investigated variables between the German and Chinese culture. First, the results indicated higher occurrence of IUD symptoms in China. Chinese subjects scored significantly higher on all ILQ dimensions than the German participants, with the exception of self-regulation where the reverse picture appeared. Second, results confirmed a positive association between Internet Use Disorder tendencies and autistic traits both in China and in Germany, although effect sizes were low to moderate (China: r =0.19 vs. Germany: r =0.36). Going beyond the literature, the present study also assessed individual differences in Internet Literacy and shows if and how variables such as technical expertise, production and interaction, reflection and critical analysis as well as self-regulation in the realm of the Internet usage influence the aforementioned association between IUD and AQ. Although the present study is limited by being of correlational nature it is discussed how the association between IUD and AQ might be explained.